PERSOALAN LIMITASI BUDAYA DAN SASTRA ISLAM - Kholil, M. (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2006)
The limitation of literature actually is still in discussion, on the other hand, it is fact that literature is the work produced by the cultural observer using language as his means. In addition to the limitation of literature, all of phenomena existing in certain society, certain period of time or certain situation are considered as literature. This point of view is not without any reasons, but it is based on the reality that literature is not independent, separated from it's society and culture which born and use it. It is clear that literature has position, role and function in society, and all of them always change from time to time and has differences among are society to another society.